The juridical-political debate of the German Parliament of March 10, 1965, as an inmediate background to the un Convention on the non-aplicability of statutory limitations to war crimes and crimes against humanitiy - Umeres Alvarez, Humberto (2020)
This writing have the purpose to reviewing and commenting on the historical debate that took place in the German Parliament, on March 10, 1965, on the Non-Applicability of Statutory Limitations to nazi crimes, as an immediate antecedent to the United Nations Convention on the Non-Applicability of Statutory Limitations to War Crimes and Crimes Against Humanity, of 1968.